2022
DOI: 10.1097/psy.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress and Hypothalamic-Pituitary-Adrenal Axis Stress Reactivity: Variations by Race and Socioeconomic Status Among Adults at Risk of Diabetes

Abstract: ObjectiveAlthough stress is posited to play a key role in health disparities, the extent to which commonly used self-report psychosocial stress measures are related to neurobiological stress processes, especially across diverse populations, is unresolved. This study examined how two measures of psychosocial stress, perceived stress and domain-specific stress, covary with the acute neurobiological stress response.MethodsThe Richmond Stress and Sugar Study includes a racially and socioeconomically diverse cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Instead, it emphasizes the importance of psychological and social factors as salient to etiopathology. In terms of how psychological factors may influence risk of type 2 diabetes, prior work has shown that depressive symptoms are correlated with biological factors such as inflammation (13)(14)(15) and hypothalamic-pituitary-adrenal (HPA) axis dysregulation (16)(17)(18), which are in turn associated with diabetes risk (19). In addition, these psychological factors are also associated with health behaviors (e.g., poor diet, physical inactivity, sleep disturbances), which are established causes of diabetes.…”
Section: Conceptual Framework: the Biopsychosocial Modelmentioning
confidence: 99%
“…Instead, it emphasizes the importance of psychological and social factors as salient to etiopathology. In terms of how psychological factors may influence risk of type 2 diabetes, prior work has shown that depressive symptoms are correlated with biological factors such as inflammation (13)(14)(15) and hypothalamic-pituitary-adrenal (HPA) axis dysregulation (16)(17)(18), which are in turn associated with diabetes risk (19). In addition, these psychological factors are also associated with health behaviors (e.g., poor diet, physical inactivity, sleep disturbances), which are established causes of diabetes.…”
Section: Conceptual Framework: the Biopsychosocial Modelmentioning
confidence: 99%